A CASE STUDY SURVEY ABOUT THE RELATIONSHIP BETWEEN COURSE CONTENT COVERAGE AND ACADEMIC PERFORMANCE OF PUPILS IN PLE IN LIRA CITY. - Ogwok , Samuel; Bakashaba, Edmand; Sendagi, Muhammad (Student’s Journal of Health Research Africa, 2023)
Background. This study aims to determine the relationship between course content coverage and the academic performance of pupils in PLE in Lira City. Methodology. A case study survey design characterized by both qualitative and quantitative methods was used. The target population of the study comprised 63 participants of which 54 respondents were selected as respondents. Two sampling techniques were employed to select the respondents of the study and these were purposive sampling and simple random sampling. Data was collected from the selected respondents using a structured questionnaire and interview guides. Results. Teachers provided course outlines to pupils at the start of the course: The mean response for this statement was 2.2, indicating that the majority of pupils disagreed or were not sure about the provision of course outlines. This suggested that there may be a lack of clear direction and guidance for the students at the start of the course. Findings showed variations in the respondents’ perceptions regarding content coverage and academic performance. While some areas, such as the teaching of basic concepts in Mathematics and provision of key concepts received higher agreement scores, areas such as English language instructions and provision of course outlines received lower agreement scores. These findings suggest areas of improvement in terms of providing comprehensive content coverage to enhance academic performance. Conclusion. There was a strong positive correlation between course content and academic performance in PLE, with a Pearson correlation coefficient of 0.871. This suggested that students who had a good understanding of the course content performed better in the PLE. Recommendation. Schools and educators should focus on providing comprehensive course content to enhance academic performance and should prioritize providing clear and detailed course outlines to help students understand the content and structure of their courses, which can improve their academic performance.